Mobi parking navigator system (cost estimation) - Mohd Naqiuddin, Harun (2013)
The peoples in UMP consist of staff and students. They come to UMP using their own vehicle and they need a parking space to park their car when they are in the class or office. This shows that the parking spaces in UMP are very important. The Mobi Parking Navigator System (MPNS) will help the user to find the nearest parking spot to their intended location. Since the MPNS is a new system, it needs help from different system to persuade the owner of the parking area to use the MPNS system. In order to convince the owner of the parking space, the MPNS (Cost Estimation) will show the potential customer the cost needed to implement the MPNS. The costs are generated from the device that will be used for MPNS.